Thromboembolic Events in the Hemodialysis Setting: Understanding Risk Profiles and Cumulative Incidences to Inform Clinical Trial Design - Angelo Karaboyas; Junhui Zhao; Laszlo B. Tanko; Kristian Tore Joergensen; Akos F. Pap; Indranil Dasgupta; Masaomi Nangaku; Michel Jadoul; Roberto Pecoits‐Filho (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background People with kidney failure have a high risk of cardiovascular morbidity/death, including thromboembolic events. Factor XIa inhibitors are a new class of anticoagulants in development that may offer antithrombotic benefits with a lower risk of incremental bleeding events than traditional therapies. We investigated major adverse vascular events (MAVEs), a relevant composite outcome for testing novel antithrombotic agents, in a large cohort of patients on hemodialysis, to better understand the key requirements to adequately design a phase 3 trial. Methods and Results We included 25 211 patients on hemodialysis for >90 days in phases 4 to 7 (2009–2021) of the DOPPS (Dialysis Outcomes and Practice Patterns Study). Atherosclerotic cardiovascular disease (ASCVD) was defined as history/presence of coronary, peripheral, or cerebrovascular disease. We estimated MAVE rates and cumulative incidence, overall and by ASCVD. Over half (52%) of the cohort met the ASCVD criteria. The MAVE hospitalization/death composite rate (per 100 patient‐years) was 6.0 in the overall cohort and 8.7 in the ASCVD subset. Three‐year cumulative incidence of MAVE was 13% in the overall cohort and 18% in the ASCVD subset. The estimated sample size to be randomized in a hypothetical trial in the ASCVD population was ≈7000 patients. Conclusions Even in the enriched ASCVD group, the observed MAVE incidence combined with a high competing risk, regulatory requirements (α=0.01), and limited recruitment pool makes feasibility of a potential randomized trial targeting MAVE reduction challenging. These results highlight key considerations and challenges for developers of novel therapies targeting systemic thromboembolic events in patients on hemodialysis.